HUBUNGAN MEKANISME COPING DENGAN INTEGRITAS AKADEMIK MAHASISWA FAKULTAS KEDOKTERAN TAHAP PREKLINIK DI UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Addinda Khila Ajnah (2020)
Academic integrity is a basic thing in education that all individuals in an academic environment must-have. The core values of academic integrity are a reflection of professional behavior which is important to comprehend. Academic integrity violations are still a problem in the academic environment. One of the factors that influence the violation of academic integrity is the pressure that can cause stress. The way individual deals with stress is called a coping mechanism. This study aims to determine the relationship between coping mechanisms and student academic integrity behavior at the pre-clinical stage of the Faculty of Medicine. The method used in this study is a quantitative method with a cross-sectional design on 128 medical students at the pre-clinic stage of the 2nd, 3rd and 4th years using a proportional stratified random sampling technique. The data from this study were collected by using a questionnaire. Data were analyzed using the Chi-Square test. The Chi-Square test showed that the P value was P = 0.102, which means it was above P <0.05. We can conclude that there is no relationship between the coping mechanism and the behavior of academic integrity of students at the pre-clinic stage Faculty of Medicine, UPN Veteran Jakarta.